Aplicación de buenas prácticas archivísticas para el mejoramiento de los procesos administrativos en el Gobierno Autónomo Descentralizado Parroquial Ángel Pedro Giler - Holguín Ponce, Alejandra Estefanía (2025)
The present research was carried out with the objective of evaluating archival practices to improve administrative processes at the Ángel Pedro Giler Parish Decentralized Autonomous Government. In this process, inductive, deductive, and analytical-synthetic methods were applied, along with techniques such as interviews and observation sheets. The results revealed that, although the current national regulations guiding document management—the Technical Rule for the Organization and Maintenance of Public Archives—exist, they are not applied within the entity’s archive due to the lack of a specific internal instrument for managing digital or physical information generated from the entity’s activities. Likewise, the archival process shows a mixed management of physical and digital formats, with a clear predominance of physical records; however, there is an evident intention to maintain some order in documentation. Consequently, current practices are based on empirical methods and lack defined technical regulations. Furthermore, the physical space allocated for the archive is limited, particularly in the storage area, where cleanliness, lighting, and ventilation are inadequate. Based on the identification of these issues, a proposal for an improvement plan was established.